Eye care service utilization and associated factors among adults in Debre Berhan Town, North Shewa, Ethiopia, 2023 - Bekele, Matiyas Mamo; Shumye, Abebech Fikade; Tegegn, Melkamu Temeselew (Frontiers in Public Health, 2024)
Introduction Globally, the utilization of eye care services varies widely, ranging from 18 to 90%. Low utilization of eye care services can lead to delayed detection of vision problems. However, there are limited data on the proportion of eye care service utilization and its associated factors in Ethiopia at the community level. Objective The objective of this study was to determine the proportion of eye care service utilization and its associated factors among adults in Debre Birhan town, North Shewa, Ethiopia. Methods Using a multistage sampling method, a community-based cross-sectional study was conducted on 960 adults in Debre Birhan town from 8 May to 8 June 2023. Binary logistic regression was performed. Variables with a p-value of less than 0.05 were considered significant. Results A total of 940 study participants participated, resulting in a response rate of 97.9%. The mean age of the participants was 54.67 years (SD ± 8.69). The proportion of good-level eye care service utilization was found to be 32.98% [95% confidence interval (CI): 29.97, 35.99]. Factors positively associated with good-level eye care service utilization included older age [adjusted odds ratio (AOR) = 1.58, 95%CI: 1.00, 2.51], higher educational status (AOR = 2.25, 95%CI: 1.25, 4.06), high family monthly income (AOR = 8.70, 95%CI: 4.99,15.18), awareness of regular eye checkups (AOR = 1.77, 95%CI: 1.15, 2.73), a history of eye disease (AOR = 2.57, 95%CI: 1.77,3.74), health insurance (AOR = 1.99, 95% CI: 1.34, 2.95), and history of spectacle use (AOR = 1.94, 95%CI:1.34, 2.80). Conclusion The study revealed that the proportion of good-level eye care service utilization was low. Older age, higher educational status, high family monthly income, awareness of regular eye checkups, a history of eye disease, health insurance, and history of spectacle use were significantly associated with a good level of eye care service utilization.